Life in the fast lane: a direct view of the dynamics, formation, and evolution of the Milky Way's bar. Issue 4 (15th October 2019) - Bovy, Jo; Leung, Henry W; Hunt, Jason A S; Mackereth, J Ted; García-Hernández, Domingo A; Roman-Lopes, Alexandre
ABSTRACT: Studies of the ages, abundances, and motions of individual stars in the Milky Way provide one of the best ways to study the evolution of disc galaxies over cosmic time. The formation of the Milky Way's barred inner region in particular is a crucial piece of the puzzle of disc galaxy evolution. Using data from APOGEE and Gaia, we present maps of the kinematics, elemental abundances, and age of the Milky Way bulge and disc that show the barred structure of the inner Milky Way in unprecedented detail. The kinematic maps allow a direct, purely kinematic determination of the bar's pattern speed of $41± 3\, \mathrm{km\, s}^{-1}\, kpc^{-1}$ and of its shape and radial profile. We find the bar's age, metallicity, and abundance ratios to be the same as those of the oldest stars in the disc that are formed in its turbulent beginnings, while stars in the bulge outside of the bar are younger and more metal-rich. This implies that the bar likely formed ${≈}8\, Gyr$ ago, when the decrease in turbulence in the gas disc allowed a thin disc to form that quickly became bar-unstable. The bar's formation therefore stands as a crucial epoch in the evolution of the Milky Way, a picture that is in line with the evolutionary path that emerges from observations of the gas kinematics in external disc galaxies over the last ${≈}10\, Gyr$ .